Ensino crítico de inglês na escola pública: para além dos muros da escola - Ribeiro, Suely Ana (2013)
In this research, I investigate how the teaching of English language based on a critical and reflective perspective developed in a public school in Goiania has happened. This research also investigates the place of language development in foreign language teaching in this context and the perception of the school community about critical teaching. To achieve this goal, I adopt a qualitative perspective and I develop an ethnographic critical research, which seeks to unveil the social and historical conditions in which the comprehension and the appreciation of social practices are formed and sustained in order to transform them for the common good. The data were collected through field notes, interviews, questionnaires, written productions and reflective narratives and they were analyzed in light of studies of Critical Pedagogy, which understand teaching as an essentially political activity committed to the problematization of knowledge, with the construction of a critical dialogue and with social practices directed towards to common welfare. This research is also based on Critical Applied Linguistics studies, which advocates in favor of an anti-hegemonic teaching practice as well as in defense of a policy of diversity and plurality, being also attentive to the political nature of language practices. The results of this study reveals that the English teaching practiced by the teacher happens through the problematization of critical issues that can be addressed with prior teaching plan or at the moment that critical events occurs in the classroom. The results also show from the point of view of the school community - participant teacher, parents, students, pedagogical team, teachers team – that there are changes in students behavior and attitudes within the classroom and in the wider social context. In addition, the students also demonstrated an increase of awareness of their own actions and concepts. In summary, this study allowed us the perception that the problematization of issues related to social life within English class can be seen as ways of developing linguistic knowledge, but also it can surpass the school boundaries and it can contribute to the empowerment of those who stays at the border of society as well as can contribute to the constitution of their identities and to individuals emancipation.